Interactive Visualization of Trivariate Georeferenced Data - Magnus Pinheiro, Tarsus; Esperança, Claudio (Journal of Information and Data Management, 2018)
This paper describes an online interactive thematic map for simultaneously visualizing up to three scalar variables and which supports data filtering, panning and zooming in levels of detail. The visual encoding of the map mixes the use of colors and textures as well as simple operations like border detection and intersection identification. The user experience is enhanced by means of queries posed through manipulation tools that produce instant visual feedback. This is possible through the high rendering rates achieved by the system through the use of GPU programming to assemble and manipulate previously rasterized tiles with location information recorded in the color space of pixels. This procedure allows the implementation of interactive animated actions and spatial data decomposition.